Intestinal inflammation and microbiota modulation impact cochlear function: emerging insights in gut-ear axis - Anna Pisani; Valentina Petito; Fabiola Paciello; Valeria Emoli; Letizia Masi; Veronica Mohamed Hizam; Pierluigi Puca; Raffaele Montuoro; Federica Del Chierico; Lorenza Putignani; Claudio Grassi; Jacopo Galli; et al. (Cell Communication and Signaling)
Abstract Background Although several evidence demonstrates a “gut–microbiota–brain axis”, suggesting a bidirectional communication between gut microbiota and the central nervous system, less is known about a possible link between the gut and the peripheral nervous system, including the inner ear. Methods Here, we investigated the impact of intestinal inflammation and the modulation of gut microbiota through fecal microbiota transplantation on hearing sensitivity. Female C57BL/6 mice were assigned to four groups: control (Ctrl), DSS-induced colitis (DSS), FMT from patients with active ulcerative colitis (FMT aUC), and FMT from patients with ulcerative colitis in remission (FMT rUC). Auditory function was evaluated by auditory brainstem responses (ABR). Morphological and molecular analyses on cochlear tissues were performed using immunofluorescence, histological staining, and Western blot to assess inflammation, oxidative stress, and blood-labyrinth barrier integrity. Donor microbiota composition was characterized by 16S rRNA sequencing, and systemic inflammation was evaluated by measuring serum lipopolysaccharide (LPS) levels. Results We found that intestinal dysbiosis is associated with functional, morphological, and molecular alterations in the cochlea, such as increased oxidative stress, inflammation, and altered blood-labyrinth barrier permeability. This leads to macrophage infiltration and immune response activation through the MyD88/NF-κB pathway. Notably, these effects were exacerbated by FMT from subjects with aUC, while FMT from patients with rUC provided a protective effect on cochlear functions. Conclusions Overall, our findings suggest that gut inflammation, microbiota alteration, or its therapeutic modulation can impact inner ear pathology: worsening gut inflammatory status negatively affects hearing sensitivity, while the restoration of gut microbiota positively impacts auditory function.